Occurrence of Phytophthora plurivora and other Phytophthora species in oak forests of southern Poland and their association with site conditions and the health status of trees - Jankowiak, R; Stępniewska, H; Bilański, P; Kolařík, M (Folia microbiologica, 2014)
Phytophthora plurivora and other Phytophthora species are known to be serious pathogens of forest trees. Little is known, however, about the presence of P. plurivora in Polish oak forests and their role in oak decline. The aims of this study were to identify P. plurivora in healthy and declining Quercus robur stands in southern Poland and to demonstrate the relationship between different site factors and the occurrence of P. plurivora. In addition, the virulence of P. plurivora and other Phytophthora species was evaluated through inoculations using 2-year-old oak seedlings. Rhizosphere soil was investigated from 39 oak stands representing different healthy tree statuses. The morphology and DNA sequences of the internal transcribed spacer regions (ITS) of the ribosomal DNA and the mitochondrial cox1 gene were used for identifications. P. plurivora, an oak fine root pathogen, was isolated from rhizosphere soil samples in 6 out of 39 stands. Additionally, Phytophthora cambivora, Phytophthora polonica and Phytophthora rosacearum-like were also obtained from several stands. The results showed a significant association between the presence of P. plurivora and the health status of oak trees. Similar relationships were also observed for all identified Phytophthora species. In addition, there was evidence for a connection between the presence of all identified Phytophthora species and some site conditions. Phytophthora spp. occurred more frequently in declining stands and in silt loam and sandy loam soils with pH ≥ 3.66. P. plurivora and P. cambivora were the only species capable of killing whole plants, producing extensive necrosis on seedling stems.
Keywords: kořeny rostlin; lesy; Phytophthora; dub (rod); Phylogeny; molekulární sekvence - údaje; stromy; Trees; Quercus; Molecular Sequence Data; Forests; Polsko; nemoci rostlin; Plant Roots; Plant Diseases; Poland; fylogeneze